The Greater Mekong Subregion economic cooperation program strategic framework 2030. (Regional cooperation strategy and programs., 2021)
The Greater Mekong Subregion Economic Cooperation Program Strategic Framework 2030 (GMS 2030) aims to strengthen regional cooperation and integration and ensure a robust recovery from the coronavirus disease (COVID 19).